Revealing the natural complexity of topographic change processes through repeat surveys and decision‐tree classification. Issue 6 (24th November 2015) - Wyrick, Joshua R.; Pasternack, Gregory B.
Abstract: Topographic change processes (TCPs) are the mechanisms by which a landscape is interpreted to be experiencing landform deformation, and are defined by the specific actions occurring within a contiguous, localized region that cause sediment to be either deposited or eroded. Past topographic change studies have mostly been focused at the site scale. The goal of this study was to identify and delineate spatially explicit TCP types across the valley width in a 34‐km long cobble‐gravel river at the scale of one‐tenth of the bankfull channel width over a period of seven to nine years. To accomplish this, a new procedure was developed that analyzes spatial patterns of topographic change evident from differencing two raster digital elevation models and accounting for sources of uncertainty, then identifying and classifying those changes using a decision tree framework that invokes the locations of those changes as they relate to the locations of specific geographic characteristics. Once mapped, TCP polygons were analyzed for areal patterns and volumetric rates of change. Results showed that 19 unique TCP types occurred and that they have organized but complex spatial patterns. Within this study segment, overbank storage processes occurred over the most area and displaced the most net volume of sediment, while cohesive bank retreat created the largest net change in topographic elevations. Analyses of the TCPs reveal that the regulated lower Yuba River (LYR) is not experiencing the expected combination of channel incision and floodplain deposition commonly reported below dams. Instead, the LYR is a dynamic valley that is still adjusting valley‐wide to the upstream dam with a diverse suite of processes that cause the channel and floodplains to scour and fill in concert. Copyright © 2015 John Wiley & Sons, Ltd.